If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -24 = 1x + 10 Reorder the terms: -24 + 3x = 1x + 10 Reorder the terms: -24 + 3x = 10 + 1x Solving -24 + 3x = 10 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -24 + 3x + -1x = 10 + 1x + -1x Combine like terms: 3x + -1x = 2x -24 + 2x = 10 + 1x + -1x Combine like terms: 1x + -1x = 0 -24 + 2x = 10 + 0 -24 + 2x = 10 Add '24' to each side of the equation. -24 + 24 + 2x = 10 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = 10 + 24 2x = 10 + 24 Combine like terms: 10 + 24 = 34 2x = 34 Divide each side by '2'. x = 17 Simplifying x = 17
| 9x-3(0)=-81 | | 8w^2+2w-1=0 | | 2+2p=6 | | 168/x=12 | | 9x-3y=-81 | | 3h^2+10h-8=0 | | n-15=31 | | 104=2v^2+8 | | x+5=4x-13 | | 12=2L+(10) | | 56=w^2+6 | | 0.25x+0.2y=350 | | 988()=1234 | | x(x+5)=-150 | | x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y |